THE STUDY ON THE POTENTIAL OF IMPLEMENTATION OF BIOCULTURAL DIVERSITY CONCEPT IN GREEN INFRASTRUCTURE DEVELOPMENT OF BUKITTINGGI CITY - Kurnia Apriliani, Sitti
Seen from an ecological perspective, cities are built from biophysics, land use mosaics, and human presence. Increasing the intensity of urban land use by human can affect the biophysics landscape and the quality of the environment as well as the urban biodiversity. To balance the physical and natural structure of the city, sustainable development was again voiced. One of the approaches is the concept of biocultural diversity (BCD). This concept was introduced as an effort to conserve biodiversity through a study of the interaction of mutual relations between nature and human in the urban green infrastructure (UGI). The development of UGI with the BCD concept is a reflexive study from several previous studies on Green Open Space (GOS) and UGI which are considered to be interpreted separately in defining human and nature. Whereas human and natural interaction is a dynamic unity that adapts to the development of the city simultaneously. The development of UGI with the BCD concept can: Support ecological connectivity and accessibility with green areas for the community; allow recreational use in green areas; improve the multifunction value of green hubs and links qualitatively; and can provide a local identity to the UGI component in the form of natural, customary and cultural values within it, so that policies on the development of UGI in an area can be adjusted to the socio-ecological characteristics of the local community. Bukittinggi City has natural and cultural potential that supports the potential of BCD study in the UGI development, so this research was conducted to examine the potential of it in Bukittinggi City. This research was conducted with a descriptive explanatory approach and using mix methods. The discussion starts by identifying the existing GOS according to local regulations which are then expanded into potential UGI. Furthermore, BCD manifestations were identified along with mechanisms of practice and policy on BCD in UGI. Last, the previous informations is used to identify the UGI development based on BCD concept. This study shows that: (1) By extending the concept of GOS to the UGI concept provide the potential for a wide variety of green hubs and links quantitatively and qualitatively; (2) There is potential for biodiversity and cultural diversity in each component of the UGI which shows the mutual interaction between nature and culture; (3) The practice of environmental management in the city of Bukittinggi begins with the role of Minangkabau adat which provides basic norms for living in harmony withiv nature and adapts according to the transformation of the city. Until now in general, this management practice has been synchronized in the regional plan document although there is no specific explanation directly related to the term of BCD; so based on the above potentials it can be seen that (4) the development of UGI in Bukittinggi City can be developed through the BCD approach, in the form of activities of conserving urban environmental elements, developing economics and sustainable ecotourism, planning and developing UGI between collaborative discipline, and so on.